No Associations Found between PGBD1 and the Age of Onset in Japanese Patients Diagnosed with Sporadic Alzheimer's Disease - Ohnuma, Tohru (S. Karger AG, 2012)
BACKGROUND/AIMS: PiggyBac transposable element derived 1 (PGBD1) encodes a molecule involved in epigenetic mechanisms that have been implicated in Alzheimer's disease (AD), and recent genome-wide association studies and meta-analyses have indicated that a single nucleotide polymorphism (SNP), rs3800324, in PGBD1 could be associated with AD and the age of onset. However, no Japanese patients were examined in these studies. The aim of the present study was to replicate the previous finding in Japanese AD cases. METHODS: We performed a case-control study (211 cases and 156 controls) to investigate the association between PGBD1 and Japanese AD using 4 tag SNPs including rs3800324. RESULTS: Single SNP and haplotype analysis showed no association between AD and age of onset, whereas genotypic and allelic frequencies of the ∊4 of apolipoprotein E (APOE) showed an association with AD as expected. CONCLUSION: In Japanese AD, we observed no influence of PGBD1, as either a risk factor or a modifier, even though APOE was associated with AD in this population.